In vivo Antimalarial and Antitrypanosomal Activity of Strychnogucine B, a Bisindole Alkaloid from Strychnos icaja - Beaufay, Claire; Ledoux, Allison; Jansen, Olivia; Bordignon, Annélise; Zhao, Senzhi; Teijaro, Christiana N.; Andrade, Rodrigo B.; Quetin-Leclercq, Joëlle; Frédérich, Michel (Planta Medica, 2018)
Strychnogucine B is a bisindole alkaloid previously isolated from Strychnos icaja that possesses promising in vitro antiplasmodial properties. This compound was synthesized in four steps from (−)-strychnine. As no acute toxicity was observed at the highest tested cumulative dose of 60 mg/kg, its in vivo antimalarial activity was determined intraperitoneally at 30 mg/kg/d in a Plasmodium berghei murine model. In the Petersʼs 4-d suppressive test, this alkaloid suppressed the parasitaemia by almost 36% on day 5 and 60% on day 7 compared to vehicle-treated mice. In addition to this interesting antimalarial activity, it showed moderate in vitro antitrypanosomal activity but no in vivo activity in an acute Trypanosoma brucei model. It was also inactive in vitro on Leishmania mexicana promastigotes. This highlights its selective antimalarial efficacy and leads to further investigation to assess its potential as new antimalarial lead compound.
Keywords: strychnogucine B; antimalarial; Plasmodium; Trypanosoma; Strychnos icaja; Loganiaceae; alkaloids; synthesis